PENGARUH PENERAPAN METODE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII SMP NEGERI 1 BAROMBONG - Jannah, Nurislahul; M, Nurhidaya; Firdaus, Andi Mulawakkan (Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to determine the application of the Think-Pair-Share method to the learning outcomes of class VIII students in the learning process of Islamic Religious Education at SMP Negeri 1 Barombong. This research uses a quantitative approach and using the type of experimental research. Then, the design used is "One Group Pretest-Posttest Design. The population in this study were students of class VIII SMP Negeri 1 Barombong and the sample consisted of one class, namely VIII C, which was taught by applying the Think-Pair-Share method. The technique used in sampling is random sampling (randomly). The data collected are data regarding student learning outcomes and then analyzed using descriptive analysis and inferential statistical analysis. The results of this study indicate that the application of the Think-Pair-Share method to the subject matter of Islamic Religious Education "Imitating the Noble Characteristics of the Prophet of Allah SWT” in class VIII C of SMP Negeri 1 Barombong, influences student learning outcomes. This is shown in the average student learning outcomes before the application of the Think-Pair-Share method in the implementation of the pretest, which is equal to 50, 93 and the average student learning outcomes after the implementation of the Think-Pair-Share method in the implementation of the posttest is equal to 81,06. Then, the results of hypothesis testing with the help of SPSS version 25.0 for Windows use the Paired Sample t-test statistic which shows a significance value of 0,000 or less than 0.05. Based on the results of this study, it can be concluded that the application of the Think-Pair-Share method has an effect on student learning outcomes because there is an increase in student learning outcomes after the application of the Think-Pair-Share method to Islamic Religious Education class VIII C SMP Negeri 1 Barombong.